Impact of the COVID‐19 pandemic on perceived cardiorespiratory fitness in athlete patients. Issue 5 (4th May 2022) - Gustus, Sarah; Moulson, Nathaniel; Churchill, Timothy W.; Guseh, James Sawalla; Petek, Bradley J.; VanAtta, Carolyn; Baggish, Aaron L.; Wasfy, Meagan M.
Abstract: Introduction: Cardiorespiratory fitness (CRF), as one of the most potent prognostic factors in medicine, is followed longitudinally to guide clinical management. Coronavirus disease 2019 (COVID‐19) pandemic‐related changes in lifestyle stand to influence CRF. Objective: To assess the influence of the pandemic on perceived CRF in athlete patients and evaluate how perceived CRF change was related to demographics, pre‐pandemic measured CRF, and current physical activity (PA). Design: Prospective cohort study, utilizing electronic survey. Setting: Tertiary care sports cardiology clinical practice. Participants: Adult athlete patients without COVID‐19 with pre‐pandemic measured CRF using cardiopulmonary exercise testing. Interventions: Not applicable. Main Outcome Measures: Perceived change in CRF since pandemic onset; association between perceived CRF change and demographics, PA, health status, and pre‐pandemic measured CRF assessed via analysis of variance (ANOVA). Results: Among 62 participants (male: 71%, 50.1 ± 12.1 years old), 40% (25/62) reported no change and 32% (20/62) reported an increase in perceived CRF since pandemic onset. Among the 27% (17/62) who reported a decrease in perceived CRF, in most (12/17), this was characterized as only mild. Demographics and pre‐pandemic measured CRF did not differ across groups of perceived CRF change. Participants with a moderate or greater decrease in perceived CRF regarded their overall health (via Euro Quality of Life Visual Analogue Scale) as worse than other groups (ANOVA, p = .001). Although total PA was similar across groups, those who had improvement in perceived CRF reported higher levels of moderate intensity PA (ANOVA, p = .008). Conclusions: The majority of participants perceived that they had maintained or improved CRF over the pandemic. Findings from this study suggest that a reduction in perceived CRF from pre‐pandemic values in athletic patients in clinical practice may not result from population‐wide pandemic changes in lifestyle. Worse health status and lower levels of moderate intensity PA were associated with perceived reduction in CRF over the pandemic in athlete patients.